Autophagy in Bone Remodeling: A Regulator of Oxidative Stress - Zhu, Chenyu; Shen, Shiwei; Zhang, Shihua; Huang, Mei; Zhang, Lan; Chen, Xi (Frontiers in Endocrinology, 2022)
Abstract: Bone homeostasis consists of bone formation and bone resorption, which maintain skeletal health. Oxidative Stress is an independent risk factor, which causes the dysfunction of bone homeostasis including osteoblast induced osteogenesis and osteoclast induced osteoclastogenesis, then leads to bone-related diseases, especially osteoporosis. Autophagy is the main system for stress responses to eliminate damaged organelles and proteins, playing a critical role in the differentiation, apoptosis, and survival of bone cells, including bone marrow stem cells (BMSCs), osteoblast, osteoclast, and osteocytes. Evidence showed that oxidative stress-induced high level of ROS causes autophagy to protect and resist cell damage or even apoptosis. Besides, ROS/FOXO3, ROS/AMPK, ROS/Akt/mTOR, and ROS/JNK/c-jun pathways are involved in the regulation of oxidative stress-induced autophagy in bone cells, including osteoblast and osteoclast. This review discussed how autophagy regulates bone formation and bone resorption from oxidative stress and summarized the potential protective mechanisms of autophagy, providing new ideas and potential therapeutic targets for osteoporosis.